Unilateral Cranial Polyneuropathy in Herpes Zoster Oticus: Infection teaching us Anatomy - Qavi, Abdul; Tiwari, Ashutosh; Maurya, Pradeep Kumar; Singh, Ajai Kumar; Kumar, Pradeep (Nepal Journal of Neuroscience, 2020)
Herpes zoster oticus or Ramsay Hunt syndrome is an uncommon neurological manifestation of herpes virus infection causing external ear rash with otalgia and facial nerve palsy. Rarely herpetic infection may present with multiple cranial nerves palsies involving VII, VIII, IX and X cranial nerves. Here we report a case of herpes zoster oticus with multiple cranial nerve palsy. This case study will help in understanding the dermatomal distribution of cranial nerves with cranial polyneuropathy due to reactivation of neurotropic herpes virus. Some interesting case reports regarding different cranial nerve involvement in herpetic infection are discussed in the table which helps in understanding the neurotropism of herpes virus.